1984
DOI: 10.1093/carcin/5.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of aflatoxin B1 carcinogenesis in rainbow trout by flavone and indole compounds

Abstract: Several compounds such as flavonoids, selenium, antioxidants and retinoids reportedly reduce the induction of cancer in experimental animals, and some have been suggested to function by affecting the mixed-function oxidase (MFO) system. The following compounds: 50 and 500 p.p.m. beta-naphthoflavone (BNF), 1000 p.p.m. flavone, 1000 p.p.m. of a tangeretin - nobilitin mixture, 1000 p.p.m. beta- ionone , 1000 p.p.m. indole-3-carbinol ( I3C ) and 2000 p.p.m. quercetin were examined for protection against aflatoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…I3C has been shown to have pronounced chemopreventive effects against development of both spontaneous (4,6) and chemically induced (1-3, 5, 7-10) tumors in rats, mice, and trout. These chemopreventive effects of I3C were reported against tumor development in mammary gland (1,4,7), liver (2,3), lung (5,8), cervix (6,9), and gastrointestinal tract (1). This observation of a chemopreventive effect of I3C in a range of species and organ sites supports the further study and development of this compound.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…I3C has been shown to have pronounced chemopreventive effects against development of both spontaneous (4,6) and chemically induced (1-3, 5, 7-10) tumors in rats, mice, and trout. These chemopreventive effects of I3C were reported against tumor development in mammary gland (1,4,7), liver (2,3), lung (5,8), cervix (6,9), and gastrointestinal tract (1). This observation of a chemopreventive effect of I3C in a range of species and organ sites supports the further study and development of this compound.…”
Section: Introductionmentioning
confidence: 95%
“…Although most animal studies with I3C and carcinogen treatment have shown chemopreventive effects (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), some experimental models have instead pointed to a tumorpromoting effect of this compound (11)(12)(13)(14). In contrast to the reported chemopreventive effects of I3C, the apparent promoting effects of I3C are highly dependent on the species, carcinogen, target organ, and exposure regimens employed (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The compound binds to the Ah receptor (AhR) and induces transcriptional activation of a wide variety of phase I/ II drug metabolizing enzymes (1,2). 5,6-BF was examined as a potential chemopreventive agent as early as the mid 1970's, and proved to be capable of inhibiting 7,12-dimethylbenzanthracene (DMBA)-induced mammary, lung, and aflotoxin B1-induced hepatocarcinogenesis (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Cruciferous vegetables and specific compounds they contain have been shown to modulate carcinogenesis in animals and humans (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Among these compounds is glucobrassicin (3-indolylmethyl glucosinolate).…”
Section: Introductionmentioning
confidence: 99%